2021
DOI: 10.5009/gnl210190
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism Risk in Asian Patients with Inflammatory Bowel Disease: A Population-Based Nationwide Inception Cohort Study

Abstract: Background/Aims Inflammatory bowel disease (IBD) is associated with the occurrence of venous thromboembolism (VTE). However, to date, there have been few studies on the risk of VTE in Asian IBD patients. We aimed to estimate the incidence of VTE in Asian IBD patients and to determine if IBD is related to increased VTE risk. Methods We performed a population-based cohort study between 2004 and 2015 using Korean National Health Insurance data. IBD and VTE were defined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
0
11
1
Order By: Relevance
“…The IBD GWAS dataset used in this study combines UC and CD, whereby we performed separate MR analyses on total IBD, UC, and CD. Unlike previous studies which reported that the risk of VTE was increased in both CD and UC patients (35)(36)(37), the MR evidence provided by this study only showed a causal relationship between UC and VTE. Notably, the meta-analysis results published by Fumery, M et al showed a significantly higher risk of VTE in UC inpatients than in CD inpatients (P = 0.0029) (14), which together with our findings suggested that UC patients may have a greater risk of VTE compared with CD patients.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The IBD GWAS dataset used in this study combines UC and CD, whereby we performed separate MR analyses on total IBD, UC, and CD. Unlike previous studies which reported that the risk of VTE was increased in both CD and UC patients (35)(36)(37), the MR evidence provided by this study only showed a causal relationship between UC and VTE. Notably, the meta-analysis results published by Fumery, M et al showed a significantly higher risk of VTE in UC inpatients than in CD inpatients (P = 0.0029) (14), which together with our findings suggested that UC patients may have a greater risk of VTE compared with CD patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous observational studies reported an increased risk of thrombosis in IBD patients ( 34 ), in accordance with our findings based on MR analysis. Furthermore, two recent cohort studies based on Asian populations reported that IBD patients are 1.80-, 1.98- and 2-fold more likely to develop PE, DVT ( 35 ), and VTE ( 36 ), respectively. A meta-analysis summarizing data from 11 observational studies covering 3,175,012 IBD patients and 920,144,253 controls showed an RR of 2.03 (95% CI: 1.72-2.39) for the occurrence of VTE in the former group ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Significant risk variables for VTE in individuals with IBD were older age, female sex, higher Charlson comorbidity index scores, cardiovascular illness, chronic kidney disease, use of steroids, and hospitalization. 19 Magro, Soares and Fernandes described in their study that inflammatory activity, hospitalization, surgery, pregnancy, disease phenotype such as fistulizing disease, colonic involvement, and severe involvement, and pharmacological therapy mainly steroids are some acquired variables that enhance the risk of VTE in IBD. Basic science, clinical, and epidemiological studies have also provided strong evidence that IBD is linked to a number of prothrombotic abnormalities, such as the activation of the coagulation system, downregulation of natural anticoagulant mechanisms, impairment of fibrinolysis, increased platelet count and reactivity, and endothelial dysfunction.…”
Section: Risk Factors and Implicationsmentioning
confidence: 99%
“…Achalasia is a rare motility disorder of the esophagus characterized by impaired relaxation of the lower esophageal sphincter 1 . Not only does this condition impose high economic burdens, but it also poses a significant risk factor for esophageal cancer 1,2 …”
Section: Introductionmentioning
confidence: 99%